2014
DOI: 10.1371/journal.pone.0109144
|View full text |Cite
|
Sign up to set email alerts
|

A Capsaicin (8%) Patch in the Treatment of Severe Persistent Inguinal Postherniorrhaphy Pain: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: BackgroundPersistent pain after inguinal herniorrhaphy is a disabling condition with a lack of evidence-based pharmacological treatment options. This randomized placebo-controlled trial investigated the efficacy of a capsaicin 8% cutaneous patch in the treatment of severe persistent inguinal postherniorrhaphy pain.MethodsForty-six patients with persistent inguinal postherniorrhaphy pain were randomized to receive either a capsaicin 8% patch or a placebo patch. Pain intensity (Numerical Rating Scale [NRS 0–10])… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…Three trials including data from 174 participants evaluated capsaicin for relief of chronic pain after inguinal hernia repair, mastectomy, and diverse procedures for cancer. All studies were at risk of bias because of issues relating to blinding of a preparation with a burning sensation and erythema.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three trials including data from 174 participants evaluated capsaicin for relief of chronic pain after inguinal hernia repair, mastectomy, and diverse procedures for cancer. All studies were at risk of bias because of issues relating to blinding of a preparation with a burning sensation and erythema.…”
Section: Resultsmentioning
confidence: 99%
“…One study was also at risk of bias owing to selective reporting. The trial assessing a single 60‐min application of a capsaicin patch (8 per cent) found no evidence of pain relief compared with placebo after 3 months. Two trials of low‐dose (0·075 per cent) capsaicin topical cream applied four times daily for 6–8 weeks reported some evidence of reduced pain intensity compared with placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Our search identified seven reviews describing different treatment options for chronic pain patients. 151 , 157 , 230 240 A 1988 landmark paper presented a treatment algorithm for chronic pain after IH repair. 230 The study authors concluded that pain persisting for 2–3 months required further investigation and treatment, starting with an IIN block at the ASIS.…”
Section: Pain: Prevention and Treatmentmentioning
confidence: 99%
“…CTS hydrogel formulations had quicker onset times but shorter durations of action compared to the poloxamer hydrogels. Topical and transdermal routes have also been investigated for the administration of other anaesthetic agents [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%